Climate resilience technology for year round vegetable production in northeastern Bangladesh - Kuddus, MA; Alam, MJ; Datta, GC; Miah, MA; Sarker, AK; Sunny, MAR (International Journal of Agricultural Research, Innovation and Technology, 2021)
A study was carried out to investigate climate resilience vegetable production prospect using tower gardening technology during the period of July 2017 to December 2017 in low-lying areas of northeastern Bangladesh (Sylhet and Moulvibazar). Total 24 participants of DFID and EU funded Suchana program (January-December’2017) were involved in the study. Two sizes of tower (a) medium size (4.5 feet diameter and 5.0 feet height) (b) small size (3.0 feet diameter and 4.0 feet height) and two types growing media protecting material (i.e. plastic bag & bamboo mat) were used separately to perform the study. To prepare the growing media (50%) soil, (40%) cow dung/compost and (10%) decomposed water hyacinth were used. Mainly two types of vegetables, climbers (i.e. bottle gourd and bitter gourd) and herbaceous (i.e. kangkong, Indian spinach, red amaranth and okra) were planted to conduct the study. The vegetable production was significantly influenced by tower size & growing media protecting materials and the highest vegetable production (84.35 kg tower-1 and 42.17 t ha-1) was recorded in medium size tower with plastic bag whose sold value was BDT 1968.50 tower-1 and BDT 98.43 Lac ha-1, respectively. In addition, the lowest vegetables production (42.08 kg tower-1 and 21.04 t ha-1) was recorded in small tower with bamboo mat that’s sold value was BDT 955.92 tower-1 and BDT 45.99 Lac ha-1, respectively. Cost-benefit ratio (2.85) was recorded in medium tower and 1.73 in small tower. In disposal pattern of vegetables major portion was used for family consumption (80% and 90%), distribution (15% and 10%) and sold (5% and 0%) in medium and small tower garden, respectively. From the result it may say that both size of tower garden were technically feasible to grow vegetable in inundated situation but medium size tower made of plastic bags performed better than bamboo mat due to less nutrient loss through leaching. The study found tower gardening on medium size tower with plastic bag could be a potential and effective option for year round vegetable production in climate vulnerable communities of Bangladesh. Int. J. Agril. Res. Innov. Tech. 11(1): 29-36, June 2021